Mechanical thrombectomy beyond the circle of Willis: efficacy and safety of different techniques for M2 occlusions. (5th July 2021) - Renieri, Leonardo; Valente, Iacopo; Dmytriw, Adam A; Puri, Ajit S; Singh, Jasmeet; Nappini, Sergio; Nencini, Patrizia; Kaliaev, Artem; Abdalkader, Mohamad; Alexandre, Andrea; Garignano, Giuseppe; Vivekanandan, Sheela; et al.
Abstract : Background: M2 segment occlusions represent approximately one-third of non-lacunar ischemic stroke and can lead to permanent neurological deficits. Various techniques are available for mechanical thrombectomy beyond the circle of Willis, but data evaluating their effectiveness and safety are lacking. Methods: A retrospective review of patients with ischemic stroke undergoing mechanical thrombectomy for M2 occlusions from 13 centers in North American and Europe was performed. Tandem or multiple-territory occlusions were excluded. The primary outcome was 90-day modified Rankin Scale and reperfusion rates across stent-retriever, direct aspiration and combined techniques. Results: There were 465 patients (mean age 71.48±14.03 years, 53.1% female) with M2 occlusions who underwent mechanical thrombectomy. Stent-retriever alone was used in 133 (28.6%), direct aspiration alone in 93 (20.0%) and the combined technique in 239 (51.4%) patients. Successful reperfusion was achieved with the combined technique in 198 (82.2%; OR 2.6 (1.1–6.9)), with stent-retriever alone in 112 (84.2%; OR 9.2 (1.9–44.6)) and with direct aspiration alone in 62 (66.7%; referencecategory). Intraprocedural subarachnoid hemorrhages (iSAH) were 36 (7.7%) and were more likely to occur in patients treated with the stent-retrievers (OR 5.0 (1.1–24.3)) and combined technique (OR 4.6 (1.1–20.9)). Good clinical outcome was achieved in 260 (61.8%) patients, while 59 (14.0%) patients died. Older age, higher baseline NIHSS (National Institutes of Health Stroke Scale), parenchymal hemorrhage and iSAH were associated with poor outcome while successful recanalization and higher baseline ASPECTS (Alberta Stroke Program Early CT Score) were associated with good outcome. No differences were found among the three techniques in terms of clinical outcome. Conclusion: Stent-retrievers and a combined approach for M2 occlusions seem more effective than direct aspiration, but with higher rates of iSAH. This leads to no detectable difference in clinical outcome at 3 months.